Vous êtes sur la page 1sur 1

u u

( x )u ' ( x ) d x ( x )u ' ( x ) d x

= =

u n +1 ( x ) n +1 u a +1 ( x ) a +1
ln u ( x )

+C +C

u ( x)

u ' ( x)

d x

+C +C

u 2 ( x) a 2 dx = u 2 ( x) + a 2 dx =
a e
u( x)

u ' ( x)

1 u ( x ) a ln 2a u ( x ) +a

u ' ( x)

1 u ( x) arctg +C a a
au( x) ln a

u ' ( x)d x

= =

+C

u( x)

u ' ( x)d x

eu ( x ) + C
cos u ( x) + C sin u ( x ) + C
ln co u ( x ) s ln sin u ( x )

sin u ( x)u ' ( x) dx = cos


u ( x )u ' ( x ) dx

tgu ( x)u ' ( x)dx = ctgu


( x )u ' ( x ) dx

+C

+C

cos 2 u ( x) dx = sin 2 u ( x) dx =

u ' ( x) a u ( x) u ' ( x) u ( x) a u ' ( x) u ( x) + a
2 2 2 2 2

u ' ( x)

tg (u ( x ) + C ctg (u ( x )) + C

u ' ( x)

dx

= = =

arcsin

u ( x) +C a

dx 2 dx

ln u ( x ) + u 2 ( x ) a 2

+C +C

ln( u ( x ) + u 2 ( x ) + a 2